Gambaran Mekanisme Koping Pada Pasien Kanker Serviks yang Menjalani Kemoterapi Di Ruang Tulip dan Poli Seruni Kanker Terpadu RSUD Arifin Achmad Pekanbaru - Ardi, Skolastika Sekarningrum Tri; Huda, Nurul; Rustam, Musfardi (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Background: Cervical cancer is one of the most common cancers affecting women in Indonesia, including in Riau Province. Chemotherapy is one of the main treatment options. Chemotherapy not only has physical effects, but also causes stress and psychological disorders that affect patients' coping mechanisms. Objective: To determine the coping mechanisms of cervical cancer patients undergoing chemotherapy at Arifin Achmad Regional General Hospital in Pekanbaru. Method: This study used a quantitative approach with a descriptive design. The sample consisted of 60 respondents selected using purposive sampling. The instrument used was the Brief COPE questionnaire to assess the coping strategies used by patients. Results: The results showed that the majority of cervical cancer patients undergoing chemotherapy tended to use problem-focused coping mechanisms (93.3%), including active coping, religious approaches, and emotional support. A small number of respondents also showed emotion-focused coping mechanisms (6.7%), including distraction and denial. Conclusion: Cervical cancer patients tend to develop problem-focused coping strategies in dealing with the physical and psychological side effects of chemotherapy. Keywords: Cervical cancer, Chemotherapy, Coping, Brief-COPE